Rúgbi na escola?!... perspectivas de uma proposta diversificada, pautada na pedagogia do esporte para a educação física escolar do ensino fundamental - Neves, Rafael Perri; Venditti Júnior, Rubens [UNESP]; Souza, Renato Aparecido; Kocian, Rafael Castro; Pereira, Mateus Camargo; Castelan, Lia Polegatto; Silva, Fabiano Fernandes da (My University, 2013)
This study aims to report the experience with elements that built Rugby at school, with the Scholarship Program Initiation to Teaching (PIBID), in the city of Muzambinho-MG-Brazil. Featuring a diversified proposal based on the theme “Collective Sports”, from the diversification of classes and promoting inclusion therein, with respect to the practice of sports and gender conflict in physical education. We also seek to establish relationships with characteristics that are objectives of primary education, with regard to the capabilities of the students present in the National Curriculum Parameters-NCPs (BRASIL, 1998). To work the theme, classes were developed based on the minimization of violence contained in the game rugby, providing a pleasurable practice of both boys and girls all together; cooperating, participating and experiencing in fair play. As a result, we had fun classes, which stimulated curiosity about the theme, the new modality and a possible expansion of the understanding of the factors involved in the world of physical education by students, offering them possibility of new practices to the same sportive modalities and adaptations at activities to attend educational context and reflections emerged from the activities and interactions.

O presente trabalho tem como objetivo relatar a experiência vivida com apresentação de elementos que proporcionaram a construção de um rúgbi da escola, ou seja, dentro do contexto escolar, junto ao Programa Institucional de Bolsas de Iniciação à Docência (PIBID) – subprojeto educação física, do Instituto Federal de Educação, Ciência e Tecnologia do Sul de Minas Gerais - IFSULDEMINAS, na cidade de Muzambinho-MG. O processo pedagógico pautou-se pela diversificação dos conteúdos ensinados e pela inclusão dos estudantes de ambos os gêneros nas mesmas. Procuramos também estabelecer relações com características tidas como objetivos do ensino fundamental, no que diz respeito às capacidades dos alunos, presentes nos Parâmetros Curriculares Nacionais – PCNs (BRASIL, 1998). Para trabalhar o tema, foram desenvolvidas aulas baseadas na minimização da violência contida no jogo, proporcionando a prática prazerosa de meninos e meninas simultaneamente; cooperando, participando e se enfrentando no fair play. Como resultado, tivemos aulas divertidas, que estimularam a curiosidade sobre o tema proposto e uma possível ampliação da compreensão dos fatores que envolvem o universo da Educação Física por parte dos alunos, oferecendo a possibilidade de novas práticas corporais aos participantes e adaptações nas práticas para atender ao contexto educacional.
Rugby at school?!... prospects of a diversified proposal guided by sports pedagogy for scholar physical education at elementary scho
Keywords: Physical education; Rugby; Inclusion; Sport pedagogy; Educação física escolar; Rúgbi; Inclusão; Pedagogia do esporte